Influence of Gaseous Hydrogen on Fatigue Behavior of Ferritic Stainless Steel – A Fatigue-life Estimation. (2015) - Schauer, Georg; Roetting, Jens; Hahn, Malte; Schreijaeg, Simone; Bacher-Höchst, Manfred; Weihe, Stefan
Abstract: The Bosch Group, a leading global supplier of technology and services develops reliable and efficient fuel cell components for future mobility solutions. This work studies the fatigue behavior of ferritic stainless steel 1.4005IA optimized for electromagnetic properties under varying environmental conditions. Fatigue-life of air-tested specimens are compared to specimens which are electrochemically hydrogen precharged and loaded in a pressurized gaseous hydrogen atmosphere. The fracture surfaces of broken specimens are investigated using optical microscope and SEM in order to analyze the failure mechanisms. Furthermore, the hydrogen contents of specimens before and after static and cyclic testing in gaseous hydrogen are measured. Based on strain controlled fatigue tests using unnotched specimens, the influence of hydrogen on cyclic material parameters is determined. Using these parameters, a fatigue-life estimation for notched specimens based on the local strain approach is carried out. Different estimation approaches are evaluated, by comparing experimental data and predicted fatigue-lifes. A modified material model, based on the four-parameter equation according to Manson, Coffin and Morrow is proposed to prescribe the influence of hydrogen on cyclic behavior of ferritic stainless steel in low gas pressure applications (up to 1 MPa). The proposed approach including the modified material model is in a good agreement to the experimental data. This opens a pathway for a reliable component design process for industrial applications.